A Review of Video Detection and Tracking Methods for Moving Objects (International Journal of Innovative Research in Computer Science & Technology, 2022)
Object detection and tracking are widely  utilized in today's society, especially for motion detection of  different objects. The initial stage in object detection is to  recognize objects in the video stream and cluster their pixels.  The classification of an item is the next crucial step in  tracking it. Computerized video surveillance, traffic  monitoring, robotic vision, gesture recognition, human computer interaction, military surveillance systems, vehicle  navigation, medical imaging, biological image analysis, and many more areas may all benefit from object tracking. The  goal of this project is to depict the different stages involved  in object tracking in a video sequence, namely object  detection, categorization, and tracking. This article compares  different approaches for different stages of tracking and  discusses several object identification and tracking methods.
Keywords: Computer; Object Discovery; Tracing; Organization; Visual Treating